Genotype-guided warfarin dosing may benefit patients with mechanical aortic valve replacements: randomized controlled study - Lee, Kyung Eun (Sci Rep, 2020)
This prospective, single-blind, randomized study was designed to evaluate the effect of genotype-based warfarin dosing compared with standard warfarin dosing in Korean patients with mechanical cardiac valves. Patients were assigned to either the genotype-based dosing group or the standard dosing group using stratified block randomization. The genotype-based dosing equation was adopted from a previous study which included VKORC1 rs9934438, CYP2C9 rs1057910, CYP4F2 rs2108622, and age. Primary outcomes included the percentage of time in the therapeutic range (pTTR): (i) during the first week following initiation of warfarin therapy, (ii) during hospitalization and (iii) until the first outpatient visit. A total of 91 patients were included in the analysis, 42 treated with genotype-based warfarin dosing and 49 treated with standard warfarin dosing. The genotype frequency differences of the three SNPs included in this study (ie, VKORC1, CYP2C9, CYP4F2), between the genotype-based dosing and standard dosing groups were not different. The genotype-based dosing group trended toward higher pTTR when compared with the standard dosing group, although this difference was not statistically significant. In patients with aortic valve replacement, TTR(Traditional) and TTR(Rosendaal) were significantly higher in the genotype-based dosing group when compared with the standard dosing group during the first week following treatment initiation [ie, 58.5% vs. 38.1% (p = 0.009) and 64.0% vs. 44.6% (p = 0.012), respectively]. Based on the results, the genotype-guided dosing did not offer a significant clinical advantage, but a possible benefit in patients with aortic valve replacement has been suggested.